PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA KELAS XI MIPA-1 PADA MATERI GELOMBANG BUNYI DAN CAHAYA DI SMA NEGERI 1 GLUMPANG BARO - Fajaruddin Fajaruddin (Jurnal Sosial Humaniora Sigli, 2022)
Education is directed at developing students' abilities, one of which is the ability to think creatively. Learning in schools still emphasizes changing thinking skills at the basic level, has not maximized students' higher-order thinking skills and often uses teacher-centered learning rather than student-centered learning. This causes a decrease in creativity and student learning outcomes. This study aims to determine the effect of project-based learning models or project-based learning on creative thinking skills and physics learning outcomes on sound and light waves in class XI MIPA-1 SMA Negeri 1 Glumpang Baro. Initial conditions illustrate that the results of the sound and light wave material test of 30 students who were able to achieve scores above the KKM were only 10 students or 33.3% with a class average of 65.5. After learning with the Project Based Learning (PjBL) model, there was an increase in learning outcomes in the first cycle test. From 30 students, there were 20 students or 66.7% who completed with an average score of 70.66. However, the results in the first cycle still did not give a significant impact, therefore the researchers again revised the planning and carried out the second cycle learning. In the second cycle showed very satisfactory results. Of the 30 students, all of them scored above the KKM or 100% complete with an average score of 86. Thus, the research implementation had reached the expected target and was stopped in cycle II.Keywords: Project-Based Learning, Creative Thinking Ability, Physics Learning Outcomes